Clinical-epidemiological aspects of severe malaria in patients at the Municipal Hospital of Cuimba, Angola - Marelys Ramirez Rabí; Elieser Imbert Puente; Ernesto Fernández Carrillo; João Landu Bamba; Antônio Ngoma (Revista Información Científica)
Introduction: Plasmodium falciparum is responsible for more than 90 % of malaria worldwide.